Photographing Washington D.C. digital field guide - Healey, John 1973- (Wiley, 2010)
The ideal companion guide for capturing awe-inspiring photos of Washington, D.C.!. Whether using a compact camera or a high-end dSLR, this companion guide provides you with detailed information for taking spectacular shots of some of the most recognizable architecture in the world. Whether you aim to capture memorable photos of the White House, U.S. Capitol, Washington Monument, Lincoln Memorial, or one of D.C.'s other many remarkable memorials, this portable resource goes where you go and walks you through valuable tips and techniques for taking the best shot possible. You'll discover suggest.
Print version record
Keywords: Architectural photography -- Handbooks, manuals, etc -- Washington (D.C.); Street photography -- Handbooks, manuals, etc -- Washington (D.C.); Photography -- Handbooks, manuals, etc -- Digital techniques; Architectural photography -- Handbooks, manuals, etc -- Technique; Photographie d'architecture; Washington (D.C.); Guides, manuels, etc; Photographie de rue; Washington (D.C.); Guides, manuels, etc; Photographie numérique; Guides, manuels, etc; Photographie d'architecture; Technique; Guides, manuels, etc; PHOTOGRAPHY; Subjects & Themes; Architectural & Industrial; Travel photography; Washington (D.C.); Amateurs' manuals; Photography; Digital techniques; Amateurs' manuals; Architectural photography; Photography; Digital techniques; Street photography; Travel; Washington (D.C.); Descriptions et voyages; Washington (D.C.); Description and travel; Washington (D.C.); Handbooks and manuals; Washington (D.C.) -- Description and travel